Laparoscopic cholecystectomy: Analysis of 300 cases - Campos Pierri, Néstor; Leal, Juan L.; Mascari, José L.; Bentancur, Bernabé; Veroli, Antonio; Da Rosa, Eduardo; Abelleira, Alfredo (Cirugía del Uruguay, 1997)
The authors analyze the first 300 cases of laparoscopic cholecistectomy and describe the main technical elements this group employs as well as a clamp far destruction and extraetion of stones which was made far this purpose.